Pengembangan Supervisi Observasi Kelas oleh Kepala Sekolah dalam Meningkatkan Kinerja Guru Di SMA Negeri 2 Merauke - Sarang, Rikardus Kristian (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2018)
The aim from the process of this research is to find, to understand, and to describe management development of class observation supervision in order to improving the teacher performance. How far the headmaster and the teacher in SMA Negeri 2 Merauke has practiced the class observation supervision. In the next process, the teacher performance will be seen the progress within few class observation supervision cycles. According to the data finding and the analysis of the research result can be concluded that some basic points: First; the class observation supervision by the headmaster must be a routine activity that has to do in SMA Negeri 2 Merauke. With this supervision class observation that continually preserved, the headmaster and the teachers will be able to understand of the most important message of the activity (the performance of teachers is increasing). Second; the teacher performance enhancement is find as: a) having maximum ability in planning and preparing the teaching-learning process, b) having maximum ability in doing the teaching learning process, c) having maximum ability in managing the class, and d) having maximum ability to evaluating the teaching-learning process.